Konvergensi Nalar Doktrin Kitab Suci Agama: Telaah Konsep Keadilan Perspektif Al-Qur’an dan Weda - Syafirin , Muhammad; Yunus, Muhammad (Alif Lam : Journal of Islamic Studies and Humanities, 2024)
All religions teach justice in its various forms and concepts. Also with the values of justice in all religions has a very substantial and principled position. No exception to Islam and Hinduism. This research uses library research methods with descriptive-analytical patterns, through text analysis approaches. It was created to examine the extent to which religions, in this context Islam and Hindu, understood the concept of justice based on the Scriptures. The Qur'an emphasizes the difference between the righteousness of mankind and that of God Himself. Unlike Hinduism, justice seems more exclusive, actionary and sometimes complex. That is, although Hindu teaches justice in the form of dharma and karmaphala, but it is bound by the law of cause and effect. It is the Lord who makes a distinction between it and the Qur'an. Moreover, the Hindu sees justice in the existence of karma acquired through the phase triangle, that is, life in the past, present, and life at rebirth. In the Qur'an, the term of absolute karma is not known. Because, God could have changed the fate of a slave if He pleased.